EDUTAINMENT WITH COMPUTER GAME AS A CHEMISTRY LEARNING MEDIA - Achmad Lutfi; Suyono Suyono; Erman Erman; Rusly Hidayah (Universitas Negeri Surabaya, 2019)
Abstract. The research aims to get answers to whether chemistry learning with computer-based games as learning media can create fun learning (edutainment). The study was conducted on students in three high schools in chemistry learning according to plan, during the learning activities were observed by students, before and after learning the learning outcomes tests and student questionnaires were conducted. The results showed that learning activities were 90.4% to 92.0% as expected, 90% to 100% of students stated that learning was fun with games as learning media, and learning outcomes had achieved 93% to 100% classical completeness. These results indicate that the use of computer-propelled games as chemical learning media can create chemical learning that pleases students and can be used by teachers as an alternative to edutainment chemistry learning